KINERJA KESELURUHAN DAN EFEK PENINGKATAN KUALITAS AIR SUSU KAMBING PERAH PAKAN SUBTITUSI YANG DI FORMULASIKAN - Nurul, Mohamad; Supartini, Nonok; Astuti, Farida Kusuma (BUANA SAINS, 2025)
This research aimed to find a solution for substitute feed for animal feed that is economically complete and increases the omega content. The research method employed a quantitative descriptive approach with four treatments, and the test livestock consisted of dairy goats of the sapera type, with a lactation period of four treatments. The treatment is as follows: P0 : control ration (concentrate Feed), P1: concentrate+5% sancha ichi beans, P2 : concentrate+10% sancha ichi beans, P3 : concentrate+15% sancha ichi beans and corn stalk forage. The results of the analysis of variance showed that the addition of sancha ichi nuts at the 5% level in the concentrate addition increased the omega-9 fatty acid content of dairy goat's milk compared to the content of fatty acids 3 and 6 at the 10% and 15% levels.